Comparative Evaluation of the Safety and Efficacy of Long-Term Use of Imidafenacin and Solifenacin in Patients with Overactive Bladder: A Prospective, Open, Randomized, Parallel-Group Trial (the LIST Study) - Masayoshi Zaitsu; Koji Mikami; Noriko Ishida; Takumi Takeuchi (Advances in Urology)
Objectives. Overactive bladder (OAB) is a chronic disease, but comparative trials of anticholinergics, which are commonly used for treatment of OAB, have generally been performed for up to 12 weeks only. There is no comparative study of a long-term intervention. Methods. We conducted a 52-week prospective randomized comparative study to evaluate the efficacy and tolerability of two anticholinergics. Results. Forty-one Japanese patients with untreated OAB were randomly assigned to imidafenacin and solifenacin groups. There was no difference in OABSS and KHQ scores between the two groups, but the severity and incidence of adverse events caused by the anticholinergics showed increased differences between the groups with time. The severity of dry mouth and the incidence of constipation were significantly lower in the imidafenacin group (𝑃=0.0092 and 𝑃=0.0013, resp.). Conclusions. This study is the first long-term trial to show differences in the properties of anticholinergics that were not detected in short-term studies. Since OAB is a chronic disease, we conclude that imidafenacin is preferable to solifenacin from a perspective of safety.